2001
DOI: 10.1002/ldr.433
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years of resolving the irresolvable: approaches to the fuelwood problem in Kenya

Abstract: Resolving the fuelwood problem in Kenya has been the cause of many debates. A review of the literature reveals the changing emphasis on the cause and effect of the problem. The dominant focus links fuelwood consumption with environmental degradation. This view has been perpetuated and reinforced by the`Woodfuel Gap' theory of supply and demand differentials, based on population growth. The demand mitigation has been addressed through the`Fuelwood Orthodoxy' approach and energy technologies. This paper shows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 22 publications
(21 reference statements)
0
23
0
Order By: Relevance
“…Thus, rural households have a complex mix of energy sources that they use at different times and for different purposes (Vermeulen et al, 2000;Madubansi, 2003), as do poor peri-urban and urban communities (Soussan et al, 1990;Davis, 1998;Brouwer and Falca˜o, 2004). Only in more affluent communities (rural and urban) do households tend to adopt a greater reliance on electricity alone (Davis, 1998;Mahari and Howorth, 2001;Brouwer and Falca˜o, 2004). The continued use of wood could be attributed to the fact that it was obtained free and was believed to cook food faster than the other fuels.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, rural households have a complex mix of energy sources that they use at different times and for different purposes (Vermeulen et al, 2000;Madubansi, 2003), as do poor peri-urban and urban communities (Soussan et al, 1990;Davis, 1998;Brouwer and Falca˜o, 2004). Only in more affluent communities (rural and urban) do households tend to adopt a greater reliance on electricity alone (Davis, 1998;Mahari and Howorth, 2001;Brouwer and Falca˜o, 2004). The continued use of wood could be attributed to the fact that it was obtained free and was believed to cook food faster than the other fuels.…”
Section: Discussionmentioning
confidence: 97%
“…The increasing distances to biomass sources in many regions [9] and the number of households that are increasingly being conditioned to purchase their needs from the markets, as well as the ever-increasing fuelwood costs demonstrate this [12]. Land tenure policies are also not being addressed in many countries, despite our new understanding that the rural energy challenge is largely on a land ownership, land management problem [13].…”
Section: Towards Sustainable Woodfuel Production and Consumptionmentioning
confidence: 99%
“…The concern, however, is the need for tenure policy to oversee innovative governance of most bushlands and woodlands-the key sources of charcoal in Kenya. The rural fuelwood problem is essentially a land-use problem [13], hence, resolving it requires the resolution of the land ownership problem through public policy reform [13]. Since most charcoal wood is obtained free of charge from rangelands, there is no incentive for commercial tree growing for charcoal.…”
Section: Land Tenure Policymentioning
confidence: 99%
“…In Mali, Benjaminsen (1997) found that locally induced deforestation caused by fuelwood use did not represent an immediate problem in rural areas. In Kenya, Mahiri and Howorth (2001) concluded that deforestation and subsequent degradation had little to do with fuelwood consumption as much was extracted from outside the forests. In their review on fuelwood consumption in developing countries, Arnold et al (2003) concluded that fuelwood supplies come from non-forest resources, hence fuelwood collection by rural dwellers has much less impact as might be concluded from forest supply of fuelwood only.…”
Section: Impact Of Fuelwood Consumption On Land Usementioning
confidence: 99%